ANALISIS PERKEMBANGAN TOKO ONLINE (E-COMMERCE) DI INDONESIA - Syaima Nida; Alfi Nurhakim; Jelita Miranda Noor Isiqamah; Nuraini (Jurnal Bisnis Digital, 2024)
This article discusses the impact of e-commerce in Indonesia. E-commerce has become a popular way for people to fulfill their needs in the midst of daily activities. With many marketplaces and online stores available, e-commerce has changed the process of buying and selling. E-commerce has made it easier for buyers to get products without going to a physical store, and for sellers to reach a wider audience. E-commerce has also helped increase the efficiency of businesses and has the potential to increase the income of small and medium-sized enterprises. The future of e-commerce in Indonesia is promising, with an estimated annual growth rate of 53.23%. Some popular e-commerce platforms in Indonesia include Bhineka, Blibli, Gramedia, Tokopedia, Bukalapak, and Shopee. Important features of e-commerce include shopping carts, discount coupons, and shipping options. Despite the benefits of e-commerce, there are also challenges, such as the need for consumer protection and the need to establish trust between buyers and sellers.